The Effect of Preheating and Non-Preheating in Cast Iron Welding Toward Mechanical Properties - Sauri, Fauzan; Mulianti, Mulianti (Universitas Negeri Padang, 2020)
Cast iron material is a material that has brittle properties and is less able to withstand stress due to the welding cycle caused by flake graphite in cast iron. Because of these problems, in connecting cast iron materials using the SMAW welding method, it is necessary to have heat treatment (preheating) to avoid the welding problems on the properties of cast iron. The purpose of this study is to determine the effect of heating and non-heating on the cast iron before the welding process. Therefore, this research will play a crucial contribution as a reference for cast iron welding researchers and cast iron welding process. The method of the research was experimental research, where the measurement results were obtained directly from the specimens. The welding was using an open V seam. The specimen used was cast iron with a thickness of 8 mm. One cast iron was given heat treatment at a temperature of 260ºC and the others did not receive heat treatment before being welded. The welding process used SMAW with CIN - 2 electrodes with a diameter of 3 mm. The test used the bending test on the face specimens according to the American Welding Society D1.1 standard. The results showed that there was an effect of the preheating treatment on cast iron, which that the non-preheating specimens were easier to fracture than the preheating specimens. Thus, it can be concluded that welding with preheating is better than welding without preheating.